Pharmacological data of cannabidiol- and cannabigerol-type phytocannabinoids acting on cannabinoid CB1, CB2 and CB1/CB2 heteromer receptors. (September 2020) - Navarro, Gemma; Varani, Katia; Lillo, Alejandro; Vincenzi, Fabrizio; Rivas-Santisteban, Rafael; Raïch, Iu; Reyes-Resina, Irene; Ferreiro-Vera, Carlos; Borea, Pier Andrea; Sánchez de Medina, Verónica; Nadal, Xavier; Franco, Rafael
Graphical abstract: Abstract: Background: Recent approved medicines whose active principles are Δ 9 Tetrahidrocannabinol (Δ 9 -THC) and/or cannabidiol (CBD) open novel perspectives for other phytocannabinoids also present in Cannabis sativa L. varieties. Furthermore, solid data on the potential benefits of acidic and varinic phytocannabinoids in a variety of diseases are already available. Mode of action of cannabigerol (CBG), cannabidiolic acid (CBDA), cannabigerolic acid (CBGA), cannabidivarin (CBDV) and cannabigerivarin (CBGV) is, to the very least, partial. Hypothesis/Purpose: Cannabinoid CB1 or CB2 receptors, which belong to the G-protein-coupled receptor (GPCR) family, are important mediators of the action of those cannabinoids. Pure CBG, CBDA, CBGA, CBDV and CBGV from Cannabis sativa L. are differentially acting on CB1 or CB2 cannabinoid receptors. Study Design: Determination of the affinity of phytocannabinoids for cannabinoid receptors and functional assessment of effects promoted by these compounds when interacting with cannabinoid receptors. Methods: A heterologous system expressing the human versions of CB1 and/or CB2 receptors was used. Binding to membranes was measured using radioligands and binding to living cells using a homogenous time resolved fluorescence resonance energy transfer (HTRF) assay. Four different functional outputs were assayed: determination of cAMP levels and of extracellular-signal-related-kinase phosphorylation, label-free dynamic mass redistribution (DMR) and ß-arrestin recruitment. Results: Affinity of cannabinoids depend on the ligand of reference and may be different in membranes and in living cells. All tested phytocannabinoids have agonist-like behavior but behaved as inverse-agonists in the presence of selective receptor agonists. CBGV displayed enhanced potency in many of the functional outputs. However, the most interesting result was a biased signaling that correlated with differential affinity, i.e. the overall results suggest that the binding mode of each ligand leads to specific receptor conformations underlying biased signaling outputs. Conclusion: Results here reported and the recent elucidation of the three-dimensional structure of CB1 and CB2 receptors help understanding the mechanism of action that might be protective and the molecular drug-receptor interactions underlying biased signaling.